Management and Outcomes of Isolated Distal Deep Vein Thromboses: A Questionable Trend toward Long-Lasting Anticoagulation Treatment. Results from the START-Register - Palareti, Gualtiero; Legnani, Cristina; Antonucci, Emilia; Testa, Sophie; Mastroiacovo, Daniela; Cosmi, Benilde; Poli, Daniela; Bucherini, Eugenio; Dentali, Francesco; Fontanella, Andrea; Mumoli, Nicola; Imberti, Davide; Falanga, Anna; Ageno, Walter; Pomero, Fulvio (TH Open, 2021)
Background Isolated distal deep vein thromboses (IDDVT) are frequently diagnosed; however, their natural history and real risk of complications are still uncertain. Though treatment is still not well standardized, international guidelines recommend no more than 3 months of anticoagulation therapy. We investigated how Italian clinicians treat IDDVT patients in their real life in our country.Methods Baseline characteristics and clinical history of the patients enrolled in the prospective, observational, multicenter START-Register for a first IDDVT or proximal DVT (PDVT) were analyzed.Results Overall, 412 IDDVT patients were significantly younger, with better renal function, and more frequent major transient risk factors, when compared with 1,173 PDVT patients. The anticoagulation duration was >180 days in 52.7% of IDDVT patients (70.7% in PDVT). During treatment, bleeding occurred in 5.6 and 2.8% patient-years in IDDVT and PDVT, respectively (p = 0082). Bleeding was more frequent in IDDVT than PDVT patients treated with warfarin (6.8 vs. 3.2 patient-years, p = 0.0228, respectively). Thrombotic complications occurred in 1.1 and 2.4% patient-years in IDDVT and PDVT patients, respectively. Analyzing together the two groups, 66.1% of bleeds and 86.1% thrombotic complications occurred after 90 days anticoagulation treatment.Conclusion The large majority of IDDVT patients received anticoagulation for more than 3 months. Most bleeding and thrombotic complications occurred after the first 90 days of anticoagulation therapy. These results indicate that an extended anticoagulation beyond 90 days in IDDVT patients is associated with increased risk of complications. Whether an extended treatment may lower recurrences after anticoagulation withdrawal should be assessed by specifically designed studies.
Keywords: isolated distal deep vein thrombosis; oral anticoagulant; bleeding; duration of treatment